2020
DOI: 10.3390/nu12113266
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal Compliance to Recommended Iron and Folic Acid Supplementation in Pregnancy, Sri Lanka: A Hospital-Based Cross-Sectional Study

Abstract: Iron deficiency anaemia during pregnancy is a common public health problem that negatively affects maternal and newborn health. This study aims to identify the rate of maternal compliance with the recommended iron and folic acid (IFA) supplementation during pregnancy and to identify factors associated with maternal compliance and non-compliance. A hospital-based cross-sectional study was conducted among 703 women at 0–4 days postpartum. The prevalence of anaemia at the initial antenatal clinic (ANC) visit and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
1
24
2
3
Order By: Relevance
“…Similarly, very low adherence to iron and folic acid supplements has been shown at Mulago National Hospital of 12% (17) and 40.9% in Tigray, Ethiopia (24). Conversely, higher levels of adherence to iron and folic acid supplements have been reported in Sri Lanka of 80.1% (25) and Tikur, Ethiopia of 63.6% (26). The adherence to IFAS in this study was very low compared to that reported in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, very low adherence to iron and folic acid supplements has been shown at Mulago National Hospital of 12% (17) and 40.9% in Tigray, Ethiopia (24). Conversely, higher levels of adherence to iron and folic acid supplements have been reported in Sri Lanka of 80.1% (25) and Tikur, Ethiopia of 63.6% (26). The adherence to IFAS in this study was very low compared to that reported in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Parents who responded ‘No’ were indicated as noncompliant with investigators’ advice. Pathirathna and colleagues also used a similar approach to investigate maternal compliance with doctors’ advice [ 29 ], whereas Obirikorang et al adopted a structured questionnaire to investigate patient treatment compliance, which comprised both medication regimen compliance (eight items) and lifestyle modification (5 items) [ 30 ]. Apart from the parent-report compliance with the investigators’ advice, we also analyzed participants’ adherence to follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of studies principally emphasized the association of maternal folic acid supplementation and fetal birth weight (33)(34)(35). Our study focused on serum folate levels before 18 weeks of pregnancy and evaluated the relationship with LBW.…”
Section: Discussionmentioning
confidence: 99%